Yield of six cultivars of passion fruits along of three years in Vargem Bonita county, Federal District, Brazil - Melo, Karina Tittoto; Manica, Ivo; Junqueira, Nilton Tadeu Vilela (Pesquisa Agropecuaria Brasileira, 2001)
The productivity of sour-passionfruit cultivars was evaluated for the purpose of obtaining productive material adapted to the Federal District conditions for consumption in natura. Maguari, CSB Marília, NJ3 Vermelho, CBS Marília x NJ3 Vermelho, Roxo Australiano and Seleção DF cultivars were evaluated during three production years in a Red-Yellow Latosol soil in the vertical stake system. Maguari presented higher seed germination rate than that of the other cultivars. The medium plant height of Seleção DF and Roxo Australiano was superior to that of the other four cultivars. Maguari showed the greatest vegetative vigor during the three-year experiment and the mindest number of lost plants due to crop decay. CSB Marília was the most precocious and the first cultivar to produce fruits. By the first harvest, CSB Marília, CSB Marília x NJ3 Vermelho, Roxo Australiano and Seleção DF were the most yielding. In the second year of harvesting, all six cultivars showed high productivity, and Seleção DF surpassed all the other cultivars, with 50 ton/ha. In the third year, in which a considerable decay occurred, Maguari presented the maximum productivity. In the three-year of production, the six cultivars showed to be superior in productivity in relation to the results of all other research ever seen in Brazil.